Antibacterial Activity of Legundi Leaf Extract (Vitex trifolia L.) with Betel Leaf Extract (Piper betle L.) against Staphylococcus aureus - Ida Bagus Oka Suyasa; Trisna Bagus Wibawa; Ni Made Defy Janurianti; Putu Diah Wahyuni (SEAS (Sustainable Environment Agricultural Science), 2022)
One of the plants that have antibacterial compounds is legundi leaves and betel leaves. The combination of the two extracts is expected to provide a synergistic effect so that it can increase the inhibition of Staphylococcus aureus bacteria. This study used the disc diffusion test method to determine the antibacterial activity. The data obtained were analyzed using the Kolmogrov-Smirnov test and continued with the one-way Anova test. The average diameter of the inhibition zone in this study ranged from 6.43 mm to 18.63 mm where legundi extract had a medium category, betel extract had a moderate to strong category, and combined extracts had a strong category. The combination of ethanol extract of legundi leaves (Vitex trifolia Linn.) with betel leaves (Piper betle L. ) has antibacterial activity against Staphylococcus aureus growth in vitro, based on the results of the one way annova test with a significance value of p < 0.05. The combination of antibacterial compounds from legundi with betel nut with a ratio of 2:1 had a greater inhibitory power than the two single extracts.